PENINGKATAN KETRAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN TEKNIK EXAMPLE NON EXAMPLE DALAM PENGEMBANGAN KOMPETENSI BAHASA INDONESIA PADA SISWA KELAS IX MTS AN-NUR NURUL FAJRI - Ahmad Syamsudin; Muhammad Masykur Baiquni (Lembaga Penerbitan dan Publikasi Ilmiah (LP2I), 2026)
This classroom action research aimed to improve the poetry writing skills of ninth-grade students at MTs An-Nur Nurul Fajri through the implementation of the Example and Non Example technique. The research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The researcher acted as the teaching practitioner, while the Indonesian language teacher served as a collaborator and observer. The data were collected through poetry writing tests, observation sheets, interviews, and documentation. The results were analyzed using descriptive qualitative and quantitative techniques, focusing on the students’ average scores, classical mastery learning percentage, and skill development throughout the intervention. The findings indicated a significant improvement in students’ poetry writing skills after the application of the Example and Non Example technique. During the pre-cycle, the average score was 60.97 with a mastery level of 25.81%. This increased to 74.09 with 45.16% mastery in Cycle I, and further improved to 78.83 with 93.55% mastery in Cycle II, showing that nearly all students successfully achieved the minimum mastery criteria. These results conclude that the Example and Non Example technique is effective in enhancing poetry writing skills. It not only strengthens students’ understanding of poetic structures and elements but also contributes to affective and psychomotor aspects such as motivation, expression confidence, activeness, and creativity in selecting diction and constructing rhyme. Therefore, the Example and Non Example technique can be used as an alternative instructional approach to improve poetry writing skills in Indonesian language learning.